2017
DOI: 10.4077/cjp.2017.bag506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carvacrol on Ca^(2+) Movement and Viability in PC3 Human Prostate Cancer Cells

Abstract: Carvacrol, a monoterpenic phenol compound, has been shown to possess various biological effects in different models. However, the effect of carvacrol on intracellular Ca²⁺ and its related physiology in human prostate cancer is unknown. This study explored the effect of carvacrol on cytosolic free Ca²⁺ levels ([Ca²⁺]i) and viability in PC3 human prostate cancer cells. Fura-2, a Ca²⁺- sensitive fluorescent dye, was used to assess [Ca²⁺]i. Cell viability was measured by the detecting reagent WST-1. Carvacrol at c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The Mn 2+ quenching data support that Ca 2+ influx occurred during diosgenin incubation. In PC3 cells, store‐operated Ca 2+ entry plays a critical role in Ca 2+ influx . Nifedipine, econazole, and SKF96365 are often applied to modulate store‐operated Ca 2+ entry in cellular studies .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Mn 2+ quenching data support that Ca 2+ influx occurred during diosgenin incubation. In PC3 cells, store‐operated Ca 2+ entry plays a critical role in Ca 2+ influx . Nifedipine, econazole, and SKF96365 are often applied to modulate store‐operated Ca 2+ entry in cellular studies .…”
Section: Discussionmentioning
confidence: 99%
“…As described previously, the measurement of cytotoxicity relied on the capacity of live cells to break down tetrazolium salts by dehydrogenases. Color density will develop proportionally to the amount of live cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[Ca 2þ ] i measurements [Ca 2þ ] i was measured as previously described. [18][19][20] Confluent cells grown on 6 cm dishes were trypsinized and made into a suspension in culture medium at a concentration of 10 6 cells per milliliter. Cell viability was determined by trypan blue exclusion.…”
Section: Solutions Used In [Ca 2þ ] I Measurementsmentioning
confidence: 99%
“…The PC3 human prostate cancer cells were used because it produces measurable [Ca 2þ ] i rises upon pharmacological stimulation. It has been shown that in this cell, [Ca 2þ ] i rises and death can be evoked by stimulation with chemicals, such as timolol, 18 carvacrol, 19 and thymol. 20 To understand the physiological significance of this Ca 2þ signal, it is important to elucidate the mechanisms underlying the signal.…”
Section: Introductionmentioning
confidence: 99%